Delayed Iron Does Not Alter Cognition Or Behavior Among Children With Severe Malaria And Iron Deficiency - Ssemata, Andrew S.; Hickson, Meredith; Ssenkusu, John M.; Cusick, Sarah E.; Nakasujja, Noeline; Opoka, Robert O.; Kroupina, Maria; Georgieff, Michael K.; Bangirana, Paul; John, Chandy C. (Pediatric research, 2020)
Malaria and iron deficiency (ID) in childhood are both associated with cognitive and behavioral dysfunction. The current standard of care for children with malaria and ID is concurrent antimalarial and iron therapy. Delaying iron therapy until inflammation subsides could increase iron absorption but also impair cognition.In this study, Ugandan children 18 months to 5 years old with cerebral malaria (CM, n = 79), severe malarial anemia (SMA, n = 77), or community children (CC, n = 83) were enrolled and tested for ID. Children with ID were randomized to immediate vs. 28-day delayed iron therapy. Cognitive and neurobehavioral outcomes were assessed at baseline and 6 and 12 months (primary endpoint) after enrollment.All children with CM or SMA and 35 CC had ID (zinc protoporphyrin concentration ≥80 μmol/mol heme). No significant differences were seen at 12-month follow-up in overall cognitive ability, attention, associative memory, or behavioral outcomes between immediate and delayed iron treatment (mean difference (standard error of mean) ranged from −0.2 (0.39) to 0.98 (0.5), all P ≥ 0.06).Children with CM or SMA and ID who received immediate vs. delayed iron therapy had similar cognitive and neurobehavioral outcomes at 12-month follow-up.